THE IMPACT OF COMPENSATION, CAREER DEVELOPMENT AND WORK ENVIRONMENT TOWARDS Y GENERATIONS EMPLOYEE'S ORGANIZATIONAL COMMITMENT AT PT. BANGUN ANUGERAH HANJAYA - Riani Leviana Anggita Sari; Irfan Noviandy Aulia (Dinasti Publisher, 2020)
This research aimed to analyze those impact which came from compensation, career development, and work environment towards organizational commitment of Y generation employees at PT. Bangun Anugerah Hanjaya. This research type was included in quantitative research with sampling method used was simple random sampling. The population was all employees at PT. Bangun Anugerah Hanjaya with numbers of 137 people. Researchers used the Slovin formula in order to gather samples of 102 people. The analysis method used multiple linear regression. The results showed that compensation, career development, and work environment together (simultaneously) had a significant impact on employee organizational commitment. Partially, compensation, career development, and work environment had a significant positive impact on organizational commitment.